Pemberantasan Korupsi dalam Perspektif Penegak Hukum - Artidjo Alkostar (Unisia, 2005)
The law is never process and Its existence free from vacuum space but it becomes and Involves with other factors, for instances social, political, economical and cultural factors. Especially in the context of law enforcement regarding the corruption. Besides, the law enforcement also concerning to jurimetrics or the scientific investigation of legal problem. In term of this, the process of law enforcement needs skill and knowledge. According to the author that the corruption in Indonesia constitutes a systemic destructed in political system mechanism, so it is an extra ordinary crimes, it needs to be deconstructed law system and law enforcement system in Indonesia, and the law enforcement in the cases of political corruption in Indonesia needs an integrated institution of law and law enforcement.